2017
DOI: 10.1037/xhp0000368
|View full text |Cite
|
Sign up to set email alerts
|

Weighted integration suggests that visual and tactile signals provide independent estimates about duration.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Copyright and reuse: City Research Online aims to make research outputs of City, University of London available to a wider audience. Copyright and Moral Rights remain with the author(s) and/or copyright holders. URLs from City Research Online may be freely distributed and linked to. City Research Online: http://openaccess.city.ac.uk/ publications@city.ac.uk Permanent repository link: City Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
(96 reference statements)
2
17
0
Order By: Relevance
“…Although these are not directly comparable to estimates from other kinds of task/analyses, these are broadly in line with previous research using untrained participants on different tasks (e.g. Ball et al, 2017;Narkiewicz, Lambrechts, Eichelbaum, & Yarrow, 2015), and they are a little above the more exactly equivalent estimates from work adopting a similar approach (but with more practised participants, with no memory manipulation; Acerbi et al, 2012). A parameter recovery simulation (Appendix B) indicated that Weber ratios could be recovered successfully using our methods.…”
Section: Model Parameters and Implicationssupporting
confidence: 78%
See 3 more Smart Citations
“…Although these are not directly comparable to estimates from other kinds of task/analyses, these are broadly in line with previous research using untrained participants on different tasks (e.g. Ball et al, 2017;Narkiewicz, Lambrechts, Eichelbaum, & Yarrow, 2015), and they are a little above the more exactly equivalent estimates from work adopting a similar approach (but with more practised participants, with no memory manipulation; Acerbi et al, 2012). A parameter recovery simulation (Appendix B) indicated that Weber ratios could be recovered successfully using our methods.…”
Section: Model Parameters and Implicationssupporting
confidence: 78%
“…Previous work (e.g. Ball et al, 2017;Hartcher-O'Brien et al, 2014) has suggested that information about duration can be combined from each of the unimodal signals comprising a bimodal stimulus, improving precision. Hence the noise that limits performance must, at some level, be independent for each modality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50,51 ), suggesting the possibility to implement the same mechanism in models for auditory classification. This additional level of redundancy in estimation would likely improve performance for scenarios that include both visual and auditory information, as has been shown in other cases where redundant cues from different modalities are combined 23,5254 . Additional redundancy in estimation would also likely reduce the propensity for the model to overestimate in scenarios that contain many times more perceptual changes than expected (such as indicated by the difference between human and model scene-wise biases Fig.…”
Section: Discussionmentioning
confidence: 82%